Drastic improvement in catalytic, optical and visible-Light photocatalytic behavior of cobalt and nickel doped TiO2 nanopowder. (5th October 2018) - Saleem, A; Imran, M; Shahzadi, A; Junaid, M; Majeed, H; Rafiq, A; Shahzadi, I; Ikram, M; Naz, M; Ali, S
Abstract: The titanium dioxide composites with cobalt (Co), nickel (Ni) and cobalt-nickel (Co-Ni) doped nanoparticles were synthesized using a sol-gel route. The structural, morphological, and physicochemical properties of mixed Co & Ni (3%) to TiO2 were characterized by XRD, FTIR, SEM, DSC-TGA, VSM, Raman and UV–vis spectroscopy. XRD pattern revealed TiO2 tetragonal-anatase phase and has confirmed a significant effect on crystallinity and particle size upon doping. The presence of strong chemical bonding and functional group at the interface of TiO2 nanoparticles was confirmed by FTIR. The increase in absorption range with different doped materials was recorded by UV–vis spectroscopy. The saturation magnetization (MS ) was higher for TiO2 relative to doped materials. However, the thermal stability of the samples at high temperature (0 to 1000 °C) was monitored using DSC-TGA. The morphology of synthesized undoped and doped TiO2 nanoparticles showed agglomerations of nanomaterials was examined using SEM. The synthesized nanomaterials have been successfully applied as nanocatalyst in degradation of methylene blue. Co-Ni doped TiO2 nanoparticles an impressive catalytic performance in the presence of reducing agent NaBH4 . This increase is attributed to augmentation of light absorption in the visible range with doping. Thus, Co:Ni:TiO2 in the presence of NaBH4 can be a promising photocatalyst in the field of wastewater treatment.